Severe diseases of the anterior segment of the eye accompanied by somatic pathology and COVID-19: clinical cases under the pandemic - O. I. Lebedev; A. V. Surov; T. Yu. Matnenko; S. Zh. Kabuldinova; O. V. Kutuzov; E. M. Naumenko (Российский офтальмологический журнал)
The article presents three clinical cases of severe pathologies of the anterior segment of the eye, which developed in patients with serious concomitant somatic diseases and COVID-19 under the pandemic. Our observations show that the SARS-CoV-2 virus can contribute to the onset of severe keratitis and keratouveitis, characterized by a long torpid course, relapses, and a poorly predicted outcome. In patients with coronavirus and severe somatic pathology, these diseases have atypical symptoms that complicate the diagnosis, are resistant to treatment, and require an extended period of convalescence. This can be explained by pronounced vascular inflammatory reactions, a possible invasion of eye tissue by viral particles, disruption of tear production, a decrease in local immune defense factors of the eye and systemic immunity, and a violation of the hemato-ophthalmic barrier. Local and general drug treatment brought weakly positive changes. The course of the disease took an undulating character. The description of the clinical cases reflects the polymorphism of symptoms and the multiorganic character of damages associated with COVID-19.